Host Range of, and Plant Reaction to, Subanguina picridis - Watson, A K (Journal of nematology, 1986)
The host range of the knapweed nematode, Subanguina picridis (Kirjanova) Brzeski, under controlled environmental conditions was extended to include, in addition to Russian knapweed, Acroptilon repens (L.) DC., plant species within the Centaureinae, and Carduinae subtribes of the Cynareae tribe of the Asteraceae family. Examination of host response to nematode infection revealed that Russian knapweed was the only highly susceptible host plant. Diffuse knapweed (Centaurea diffusa Lam.) was moderately susceptible, and other plants which formed galls were resistant to S. picridis